2009
DOI: 10.1503/cmaj.080570
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with suspected drug-facilitated sexual assault

Abstract: Since the mid-1990s, there has been a growing number of unconfirmed reports of assailants surreptitiously using prescription and nonprescription drugs to induce disinhibition, sedation and amnesia to facilitate rape. 1 This type of victimization is most commonly referred to as drug-facilitated sexual assault. Although flunitrazepam, in particular, has been maligned as a "date rape drug," 2 many other easily accessible substances have reportedly been used to facilitate sexual assault, including alcohol and alpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 19 publications
2
46
1
4
Order By: Relevance
“…In a Canadian study by Du Mont et al of 184 individuals 16 years and older who met the criteria for DFSA, 86% had consumed alcohol before the assault, and one-quarter of the sample had used over-the-counter prescription or street drugs in the 72 hours before the test collection. 35,36 Unexpected (ie, no known history of drug exposure to the specific drug) positive toxicology results were found in 49% of the suspected DFSA cases; results showed cannabinoids (40%) and cocaine (32%) most frequently. Similar individual studies and systematic reviews 37 from the United States, Canada, United Kingdom, Australia, and other countries have reported that less than 2% of cases of DFSA are associated with common date rape drugs.…”
Section: Use Of Substancesmentioning
confidence: 99%
“…In a Canadian study by Du Mont et al of 184 individuals 16 years and older who met the criteria for DFSA, 86% had consumed alcohol before the assault, and one-quarter of the sample had used over-the-counter prescription or street drugs in the 72 hours before the test collection. 35,36 Unexpected (ie, no known history of drug exposure to the specific drug) positive toxicology results were found in 49% of the suspected DFSA cases; results showed cannabinoids (40%) and cocaine (32%) most frequently. Similar individual studies and systematic reviews 37 from the United States, Canada, United Kingdom, Australia, and other countries have reported that less than 2% of cases of DFSA are associated with common date rape drugs.…”
Section: Use Of Substancesmentioning
confidence: 99%
“…Similarly, a list of seven criteria was developed to identify those who thought they had been sexually assaulted, but were unable to recall details (e.g., woke unclothed or to find clothing in disarray; unexplained body fluids such as semen found on body; unexplained anogenital injuries). For this study, a case was defined as a person who reported at least one valid reason for suspecting having been drugged and at least one reason for suspecting having been sexually assaulted (see 16 for more details).…”
Section: Methodsmentioning
confidence: 99%
“…Available studies have concentrated on Western countries (see Du Mont et al, 2009;Fisher, Daigle, Cullen, & Turner, 2003;Pino & Meier, 1999;Ruback, Menard, Outlaw, & Shaffer, 1999;Thompson, Sitterle, Clay, & Kingree, 2007;Wolitzky-Taylor et al, 2011), and non-Western societies have received limited attention. Ghana, a developing postcolonial society, is no exception to this academic neglect.…”
Section: Introductionmentioning
confidence: 99%